Integrating Prayer and Mathematics in Value-Based Mathematics Education - Surur, Agus Miftakus; Pujilestari, Sri; Ridwanulloh, M. Ubaidillah (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3813, 2025)
This study aims to explore the integration between mathematics and Islamic prayer through the conceptual pillars of patterns, numbers, and abstraction, framed within a value-based learning approach. Mathematics, as a discipline concerned with numerical operations, structural patterns, and abstract reasoning, provides a logical framework that can be meaningfully connected to spiritual practices. Prayer, as an act of devotion and direct communication with Allah SWT, embodies structural regularity, numerical precision, and abstract spiritual intention, making it a fertile context for contextualized mathematics instruction. Using a qualitative-descriptive approach with a literature study method, this research analyzes Qur’anic verses, classical tafsir, and scholarly works on mathematics in Islamic tradition. The findings reveal that the sequence and symmetry of prayer movements, the fixed counts in rakʿah and dhikr, and the unseen dimensions of intention and focus in prayer parallel mathematical principles of pattern recognition, cardinality, and abstraction. The integration of these elements into mathematics lessons can enhance cognitive skills (pattern recognition, calculation, abstraction), foster positive affective engagement by linking learning to meaningful religious contexts, and cultivate spiritual values such as discipline, mindfulness, and faith. This study concludes that mathematics and prayer are complementary pathways to understanding order in both the physical and spiritual realms, supporting the holistic objectives of Islamic education.